Clinician and patient experience of neurology telephone consultations during the COVID-19 pandemic - Nakornchai, Tagore; Conci, Elena; Hensiek, Anke; Brown, J William L (Postgraduate medical journal, 2022)
BackgroundTelephone consultations are already employed in specific neurological settings. At Cambridge University Hospitals, the COVID-19 pandemic initially prompted almost all face-to-face appointments to be delivered by telephone, providing a uniquely unselected population to assess.ObjectivesWe explored patient and clinician experience of telephone consultations; and whether telephone consultations might be preferable for preidentifiable subgroups of patients after the pandemic.MethodsClinicians delivering neurological consultations converted to telephone between April and July 2020 were invited to complete a questionnaire following each consult (430 respondents) and the corresponding patients were subsequently surveyed (290 respondents). The questionnaires assessed clinician and patient goal achievement (and the reasons for any dissatisfaction). Clinicians also described consultation duration (in comparison to face to face) while patients detailed comparative convenience and preference.ResultsThe majority of clinicians (335/430, 78%) and patients (227/290, 78%) achieved their consultation goals by telephone, particularly during follow-up consultations (clinicians 272/329, 83%, patients 176/216, 81%) and in some disease subgroups (eg, seizures/epilepsy (clinicians 114/122 (93%), patients 71/81 (88%)). 95% of telephone consultations were estimated to take the same or less time than an equivalent face-to-face consultation. Most patients found telephone consultations convenient (69%) with 149/211 (71%) indicating they would like telephone or video consultations to play some role in their future follow-up.ConclusionTelephone consultations appear effective, convenient and popular in prespecified subgroups of neurological outpatients. Further work comparing telephone, video and face-to-face consultations across multiple centres is now needed.